2008
DOI: 10.1002/ptr.2471
|View full text |Cite
|
Sign up to set email alerts
|

Use of phytotherapy in dentistry

Abstract: Over the past decade, interest in drugs derived from medicinal plants has markedly increased. This study was aimed at a literature review focusing on studies investigating herbal drugs and other natural products, as well as their therapeutic application, side effects and possible drug interactions. Few studies were found to support their rational use in dentistry. Since there is an increasing use of phytotherapeutic agents in dentistry, further studies are needed to evaluate their safety and effectiveness for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 63 publications
1
66
0
13
Order By: Relevance
“…Many invitro studies have shown anti-inflammatory, antioxidant, anticarcinogenic, antimicrobial potential of various plant products [15]. Subramaniam et al, determined the effect of aqueous and organic extracts of three types of tea (green, oolong, and black tea) on the growth of S. mutans.…”
Section: Resultsmentioning
confidence: 99%
“…Many invitro studies have shown anti-inflammatory, antioxidant, anticarcinogenic, antimicrobial potential of various plant products [15]. Subramaniam et al, determined the effect of aqueous and organic extracts of three types of tea (green, oolong, and black tea) on the growth of S. mutans.…”
Section: Resultsmentioning
confidence: 99%
“…The interest in naturally derived biological compounds that may have the potential to be used as therapeutics in medicine and dentistry is rising [13,31]. There are previous published studies on the activity of tea components against bacteria responsible for oral diseases.…”
Section: Microbiological Assays – Determination Of Minimum Inhibitorymentioning
confidence: 99%
“…The toxicity of a dental material can be evaluated by in vitro tests in animals and humans. When a new product is developed, it is necessary to perform laboratorial tests with it, allowing safe clinical applications, and providing subsides for its use by health professionals and clinics proving its non-toxicity to tissue [11,12].…”
Section: Introductionmentioning
confidence: 99%